REKAYASA ALAT FILTER PENGOLAHAN LIMBAH CAIR TAHU DENGAN PENAMBAHAN DAUN BAMBU (Bambusa Sp) DAN ARANG BAMBU TERHADAP PENURUNAN KADAR TSS DAN BOD - Rois, Ibnu; Dwisukmana, Ismy Putri; Santjoko, Herman (Poltekkes Kemenkes Bengkulu, 2023)
Many tofu home enterprises in Indonesia lack an IPAL treatment system, resulting in the direct discharge of liquid waste into rivers, which has an effect on the devastation of aquatic ecosystems and serves as a source of disease seeds. TSS levels and BOD levels have been set at 200 mg/l and 150 mg/l, respectively, in accordance with DIY Regional Regulation No. 7 of 2016 about the quality standards for the quality of tofu liquid waste. X tofu liquid waste has TSS levels of 1004 mg/l and BOD levels of 3780 mg/l, according to preliminary testing. Understanding how the addition of bamboo leaves (Bambusa Sp) and bamboo charcoal to three filtration methods for processing tofu liquid waste reduces the levels of TSS and BOD. The study's research methodology was a quasi-experiment using a pre-post test and control group design. Using the t-test, one-way anava test, and shapiro-Wilk test for inferential analysis. Using 20 cm bamboo leaves and 30 cm bamboo charcoal, treatment 3 reduced TSS levels by 54.44 percent and BOD levels by 66.21 percent. Treatment 1 used 30 cm bamboo leaves and 20 cm bamboo charcoal to reduce TSS levels by 69.81 percent and BOD levels by 69.31 percent. Treatment 2 used 25 cm bamboo leaves and 25 cm bamboo charcoal to reduce TSS levels by 61.33 percent and BOD levels by 66.84 percent. The TSS and BOD levels show sig.> 0.05 in the one-way anava test, indicating that there is a significant difference between the 3 filter treatments. The biggest reduction in TSS and BOD levels occurs in treatment 1, which also uses additional bamboo leaf media and bamboo charcoal for filtration.